1941
DOI: 10.6028/jres.027.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrochloric acid and salts on the absorption of light by beta-naphthoquinonesulfonic acid

Abstract: In order to evaluate t he effects of hydrochloric acid and neutral salts on the absorption of light by an organic acid dye, spectrophotometric measurements were made of a series of solutions of hydrochloric acid and of neutral salts plus hydrochloric acid, each containing 3 X 10-4 M I'l-naphthoquinonesulfonic acid.The dye in these solutions showed small differences in spectral absorption. Similar differences may contribute to the changes of absorption shown by true indicators . Most of the data were compatible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1943
1943
2013
2013

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…The discussion below seems to eliminate the possibility that repression of the ionization of the sulfonate group accounts for these phenomena. As metacresolsulfonphthalein at pH 7.2 to 9 also shows such shifts of the absorption bands in concentrated salt solutions, we can conclude that the specific salt effect of the concentrated hydrochloric acid is due to the alteration of the spectral properties of the indicator chiefly by the change in the surrounding electrical field of the solutions [8]. The transmittancy values were read at even wavelength intervals from the graph sbeet and then cor rected to their true wavelengths.…”
Section: • 330 Journal Of Research Of the National Burea1t Of Standardsmentioning
confidence: 99%
See 2 more Smart Citations
“…The discussion below seems to eliminate the possibility that repression of the ionization of the sulfonate group accounts for these phenomena. As metacresolsulfonphthalein at pH 7.2 to 9 also shows such shifts of the absorption bands in concentrated salt solutions, we can conclude that the specific salt effect of the concentrated hydrochloric acid is due to the alteration of the spectral properties of the indicator chiefly by the change in the surrounding electrical field of the solutions [8]. The transmittancy values were read at even wavelength intervals from the graph sbeet and then cor rected to their true wavelengths.…”
Section: • 330 Journal Of Research Of the National Burea1t Of Standardsmentioning
confidence: 99%
“…Hence, as expressed linearly in eq 2, if a mixture of these two forms alone determines the observed absorp&If polar states (electronic tatitomers orelectromers) ofeacb ion, indicated by [+) and [-) signs in figUre 1, are present in instantaneous equilibrium witb tbe nonpolar forms. tbe absorption bands .may still be' used at any given temperature to calculate tbe over-all values of a and (1-a) for tbe red and yellow ions, including tbeir natural polar states or tbose "induced" by other ions [1,4,7,8 tion curve in their overlapping regions of spectral absorption, the isosbestic point must r emain unchanged with respect to both index and wave number for all stages of the color transformation. This may not be true when specific salt effects, association, or colored impurities affect this part of the spectrum, as shown in.…”
Section: Computation Of the Percentages Of The Red And Yellow Forms Omentioning
confidence: 99%
See 1 more Smart Citation
“…It may be concluded that the same group in indicators of similar structure will likewise be completely dissociated in dilute solutions, a conclusion previously arrived at by Wingfield and Acree [1]. An extension of this conclusion to more complex compounds must be made with caution, however, since sulfonic acids of large molecular weight have a tendency to exhibit colloidal characteristics.…”
Section: Calculations Of the Ph Values Of The Acid-salt Mixturesmentioning
confidence: 75%
“…The emf of this cell at a pressure of 1 atmosphere of hydrogen is given by E=Eo-RJ In(l4Iacl)=Eo-RJ In (jHfClmHmd, (1) in which E is the measured emf in international volts; EO is the potential of the silver-silver-chloride electrode in international volts for unit activity of hydrochloric acid; a, m, andf represent, respectively, the activity, molality, and activity coefficient of the ionic species denoted by subscripts; and R, T, and F have their usual significance. In table 1 values of the observed emf corrected to unit hydrogen pressure in the usual manner r131 are given for the temperatures of 10°, 25°, 40°, and 60° C and for the various solutions of concentrations recorded in columns 2 and 3.…”
Section: Electromotive-force Measuremen Tsmentioning
confidence: 99%